Complete mitochondrial genome of the Red Keelback (Pseudagkistrodon rudis Boulenger, 1906). Issue 10 (3rd October 2021) - Zhou, Yi-Nan; Zhang, Chuan-Ying; Zhang, Zheng-Hua; Zhong, Jun-Jie; Ding, Guo-Hua
Abstract: The Red Keelback ( Pseudagkistrodon rudis Boulenger, 1906) is widely distributed in the southern of China. The complete mitochondrial genome (mitogenome) of P. rudis was determined for the first time by using next-generation sequencing. The size of assembled mitogenome for P. rudis was 19, 150 bp, which included 13 protein coding genes ( PCGs ), 22 tRNAs, two rRNAs and two control regions (d -loop 1 and d -loop 2). The Bayesian tree showed that P. rudis and Rhabdophis tigrinus have a closed relationship. These results can provide data for phylogeny and molecular classification of the genus.